2013
DOI: 10.1002/jsfa.6085
|View full text |Cite
|
Sign up to set email alerts
|

Proximate composition and lipid stability of dourado (Salminus brasilensis, Cuvier, 1817) fillets exposed to different levels of ammonia and oxygen in vivo

Abstract: These results indicate that the in vivo exposure to high ammonia levels may reduce the quality and stability of dourado fillets.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
2
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 32 publications
1
2
0
1
Order By: Relevance
“…Besides, the species effect on pH obtained in this study has already been mentioned by several authors (Howgate, 2009 ;Ozogul, 2010 ;Li et al, 2011 ;Veeck 2013 ;Wongwichian et al, 2013 ;Kakele et al, 2017).…”
Section: Technological Qualities Of Fishsupporting
confidence: 84%
“…Besides, the species effect on pH obtained in this study has already been mentioned by several authors (Howgate, 2009 ;Ozogul, 2010 ;Li et al, 2011 ;Veeck 2013 ;Wongwichian et al, 2013 ;Kakele et al, 2017).…”
Section: Technological Qualities Of Fishsupporting
confidence: 84%
“…1‐Monopalmitin is a kind of lipids with the function of storing energy, and also acts as a structural component of cell membranes 37 . It was reported that the content of fat was decreased and the tissue susceptibility to lipid oxidation was increased after high‐ammonia exposure 38 . The down regulated of 1‐Monopalmitin in HG maybe indicated that lipolysis was activated and the integrity of the cell membrane was destroyed by high concentration of ammonia exposure.…”
Section: Discussionmentioning
confidence: 99%
“…Microbial decomposition of organic matter in water results in increased levels of ammonia . Ammonia, especially in an un‐ionized form, is toxic for commercial fish . High concentrations of environmental ammonia have been reported to affect survival, growth, metabolism, ions and the hormonal balance of aquatic animals …”
Section: Introductionmentioning
confidence: 99%